Solo Songs by Count Julijan Pejačević in the Našice Local History Museum - Andrea Rakitić (Arti Musices)
The Pejačević Collection of the Našice Local History Museum holds 28 solo songs by Count Julijan Pejačević (1833 – 1906) in the German language for voice and piano. Although he is remembered primarily as a royal chamberlain and family historian, he was also a pianist and a composer. His musical oeuvre consists of at least 70 works (though some sources would point to far more), including solo songs and piano pieces, most of which are today lost due to a plethora of reasons concerning the history of the Pejačević family library. The collection of solo songs in question is the only known presently surviving part of Count Julijan’s musical oeuvre. This paper aims to shed light on the compositional work of another member of the Pejačević family by presenting and interpreting the results of the analysis of his surviving solo songs (Op. 56 – Op. 83) through a selection of examples.